Post- Method Pedagogy: Towards New Horizon of English Language Teaching - Sarmatha, S. (Department of English Language Teaching, University of Jaffna, 2019)
A method can be envisaged as a collective classroom techniques and pedagogical approaches grounded in the English Language Teaching and Learning context of institutionalized milieu. Chronologically and globally, several methodologies and approaches have been evolved and implemented in language classrooms and there are paradigm shifts occurred in terms of enhancing English Language learning and pedagogy. According to the postmethodists, post methods have evolved because of the dissatisfaction with the traditional methods. In the neo globalized world, the conventional methods and approaches of English Language Teaching seems inadequate and several aspects of language learning must be considered. Consequently, it is vital to explore the needs to move beyond methods and the practice of English Language Teaching in the post- method era. The aim of this paper is implementing macro strategies in the English as a Second Language (ESL) classrooms. The focus of the macro strategies is fostering the concepts of 'maximising learning opportunities' and 'promoting learner autonomy'. Emerging gradually over the years, post methods have been accelerating learner autonomy than the conceptualised conventional methods and the plausibility for the paradigm shift of English language teaching can be envisioned in the continuum of eclecticism and pragmatism. Thus, this paper focuses on the practicality and possibility of the post- method pedagogy in the arena of English Language teaching. This study is based on mixed methods that comprise classroom observation, interviews, pre-test and post-test. The target group of this study is the first-year students in the faculty of Business studies in Vavuniya campus. Thirty students participated and the opportunities to learn and use the language have been constrained for almost all the students. Data were collected through classroom observation, interviews with the participants and the results of the pre-test and post-tests. During the pre-test session the designed lesson was taught by conventional methods and in the post - test session the same lesson was taught by exploiting macro strategies of post methods. The finding of this study shows that the participants scored more when exploiting the synergistic macro strategies than in the conventional method of pedagogy.
Keywords: Post - methods; Learner autonomy; Pedagogy; Macro strategies; Pragmatism